The Paris orphan - Lester, Natasha, 1973- (Forever, 2019)
1942. When American model Jessica May arrives in Europe to cover the war as a photojournalist for Vogue, most of the soldiers are determined to make her life as difficult as possible. But three friendships change that. Journalist Martha Gellhorn encourages Jess to bend the rules. Captain Dan Hallworth keeps her safe in dangerous places so she can capture the stories that truly matter. And most important of all, the love of a little orphan named Victorine gives Jess strength to do the impossible. But her success will come at a price. 2005. Decades after World War II, D'Arcy Hallworth arrives at a beautiful chateau to curate a collection of famous wartime photos by a reclusive artist. It's the opportunity of a lifetime, but D'Arcy has no idea that this job will uncover decades of secrets that, once revealed, will change everything she thought she knew about her mother, Victorine, and alter D'Arcy's life forever.